Development of High Pressure Thin Layer Chromatographic Method for Simultaneous Estimation of Ranitidine HCl and Domperidone in Their Combined Dosage Form - S. Charde , Manoj; G. Walode, Sanjay; R. Tajne, Madhukar; V. Kasture, Avinash (Asian Journal of Chemistry, 2016)
An accurate and precise high pressure thin layer chromatographic method for simultaneous estimation of ranitidine HCl and domperidone in their combined dosage form has been developed. The study employs a silica gel 60GF254 on aluminium foil and a mobile phase comprising methanol : 1,4-dioxane (4 : 6 v/v). The detection was carried out at 282 nm. The linear detector response for ranitidine HCl was observed between 3.0 to 50 μg/mL while for domperidone 0.2 to 3.5 μg/mL. The recovery study was carried out by standard addition method. The recovery was found to be 100.25 ± 0.859, 100.78 ± 0.592 for ranitidine HCl and 100.29 ± 0.394, 99.54 ± 0.436 for domperidone.